Deterring Future Incidents of Intimate Partner Violence: Does Type of Formal Intervention Matter?. (August 2016) - Broidy, Lisa; Albright, Danielle; Denman, Kristine
Few studies examine the comparative effectiveness of different formal interventions for domestic violence. Using arrest and civil protection order data, we compare three intervention scenarios (arrest, civil protection order, and both). Results suggest that intervention type has no substantive influence on the odds of reoffending. However, subsequent domestic violence is significantly associated with offender age, sex, and prior offense history as well as victim age and sex. We discuss our findings and their policy implications, noting that responding agencies should be sensitive to the characteristics that increase the odds of reoffending among those they come into contact with.